Maturity class and P effects on soya bean grain yield in the moist Savanna of west Africa - Ogoke, I.; Carsky, R.; Togun, A.; Dashiell, Kenton E. (Wiley, 2003)
Field trials were replicated at four sites in the moist savanna ecological zone of West Africa to study the effect of maturity class and phosphorus (P) rate on grain yield and total protein yield (TPY) of some new soya bean varieties. Grain yield and TPY averaged 1.43 Mg ha−1 and 587 kg ha−1, respectively. Without P application grain yield and TPY were not significantly different among the varieties. In addition, at zero P treatment, grain yield and TPY were not significantly different among three sites where available P was 6.2 mg kg−1 or less. P application depressed grain yield and TPY at a site where the available soil P was high (16.2 mg kg−1). With P application grain yield and TPY were in the range of 1.2–2.28 Mg ha−1 and 505–948 kg ha−1, respectively, for the varieties compared with 0.99–1.12 Mg ha−1 and 454–462 kg ha−1 when P was not applied. The response of grain yield to 30 kg P ha−1 was substantial at Gidan Waya (113 %), Kasuwan Magani (63 %) and Fashola (60 %), three sites where available soil P was low. The application of 30 kg P ha−1 increased grain yield by 21 % in early, 26 % in medium and 58–70 % in the late varieties. Significant variety by P rate interaction effects were observed on grain yield and TPY but not on grain protein concentration (GPC). TPY showed greater response to P in the late varieties than in the early or medium. While seed size correlated significantly and positively with GPC, P application had no significant effect on GPC.